Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acsearthspacechem.1c00343
|View full text |Cite
|
Sign up to set email alerts
|

Rate Constant and Branching Ratio for the Reactions of the Ethyl Peroxy Radical with Itself and with the Ethoxy Radical

Abstract: The self-reaction of the ethyl peroxy radical (C 2 H 5 O 2 ) (R1) has been studied using laser photolysis coupled to a selective time resolved detection of two different radicals by continuous wave cavity ring-down spectroscopy (cw-CRDS) in the near-infrared range: C 2 H 5 O 2 was detected in the Ã-electronic transition at 7596 cm -1 , and HO 2 was detected in the 2 1 vibrational overtone transition at 6638.21 cm -1 . Radicals were generated from pulsed 351 nm photolysis of C 2 H 6 / Cl 2 mixture in presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 43 publications
(127 reference statements)
0
14
0
Order By: Relevance
“…The current IUPAC database therefore recommends, for the C 2 H 5 O 2 self-reaction, based on the analysis of stable end products, a yield of 0.63 for the alkoxy path (1), 0.37 for the molecular path (2) and 0 for the dimer path (3) [ 24 ]. More recent studies directly measuring the radical yield (1) from the self-reaction of C 2 H 5 O 2 found only a minor yield of 0.28 [ 25 ] and 0.31 [ 26 ] for the alkoxy path (1), in strong disagreement with the IUPAC recommendation. A possible explanation for this strong disagreement could be a higher yield of the dimer path (3), which could, due to its instability, appear in the stable end-product studies as a radical path.…”
Section: Introductionmentioning
confidence: 98%
“…The current IUPAC database therefore recommends, for the C 2 H 5 O 2 self-reaction, based on the analysis of stable end products, a yield of 0.63 for the alkoxy path (1), 0.37 for the molecular path (2) and 0 for the dimer path (3) [ 24 ]. More recent studies directly measuring the radical yield (1) from the self-reaction of C 2 H 5 O 2 found only a minor yield of 0.28 [ 25 ] and 0.31 [ 26 ] for the alkoxy path (1), in strong disagreement with the IUPAC recommendation. A possible explanation for this strong disagreement could be a higher yield of the dimer path (3), which could, due to its instability, appear in the stable end-product studies as a radical path.…”
Section: Introductionmentioning
confidence: 98%
“…Despite several efforts to measure the branching ratio between reactions and , there is still substantial uncertainty in these branching ratios even at room temperature, spanning from 27:72 to 74:26. Recent studies by Shamas et al and Noell et al indicates lower branching to reaction (∼30%) at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Despite several efforts to measure the branching ratio between reactions and , there is still substantial uncertainty in these branching ratios even at room temperature, spanning from 27:72 to 74:26. Recent studies by Shamas et al and Noell et al indicates lower branching to reaction (∼30%) at room temperature. Considering the uncertainty in the branching ratios at high temperatures, we first assumed equal branching to reactions and (50:50).…”
Section: Resultsmentioning
confidence: 99%
“…The setup has been described in detail before [32][33][34][35][36][37] and is only briefly discussed here. The setup consisted of a 0.79 m long flow reactor made of stainless steel.…”
Section: Methodsmentioning
confidence: 99%